Moyamoya disease is associated with endothelial activity detected by anti-nestin antibody - Chmelová, Jana; Kolář, Zdeněk; Procházka, Václav; Čuřík, Romuald; Dvořáčková, Jana; Širůček, Pavel; Kraft, Otakar; Hrbáč, Tomáš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2010)
AIM: To describe the case history and new histopathological findings of a young woman suffering from moyamoya disease. METHODS: The patient underwent brain computed tomography, magnetic resonance imaging and brain angiography. Vessel samples of a. temporalis superficialis were processed by standard histopathological and immunohistochemical methods by analysis of VEGF, VEGFR and nestin expression. RESULTS: Brain angiography revealed both internal carotid artery stenoses and stenoses of the anterior cerebral arteries. Stenotic parts of vessels were accompanied by coiled and elongated vessels with a picture of "smoke puffs carried away by breeze" after contrast medium application. Histological examination showed: obstruction of lumen, fibrocellular intimal thickening, tortuosity and disruption of internal elastic lamina. Imunohistochemistry confirmed a defect of the internal elastic membrane of the muscular arteria and progressive intimal thickening accompanied by abnormal smooth muscle cells and, VEGF/VEGFR expression in intima. Nestin positivity in endothelium of arteria indicated that endothelial cells are activated. CONCLUSION: We found that the endothelium of affected vessels is nestin positive. This, together with the finding of VEGF/VEGFR expression, might suggest an active angiogenetic process We present a new conception of pathogenesis but further studies with higher number of patients are necessary to elucidate the role of these growth factors in the moyamoya disease.
Keywords: moyamoya nemoc; imunohistochemie; vaskulární endoteliální růstové faktory; Humans; Carotid Arteries; arteriae carotides; Immunohistochemistry; lidé; financování organizované; Endothelium, Vascular; Vascular Endothelial Growth Factors; receptory vaskulárního endoteliálního růstového faktoru; proteiny intermediálních filament; Financing, Organized; Female; Receptors, Vascular Endothelial Growth Factor; cévní endotel; Adult; dospělí; Moyamoya Disease; Intermediate Filament Proteins; ženské pohlaví; proteiny nervové tkáně; Nerve Tissue Proteins